Lack of Social Audit : Black Hole in MNREGS - Saklani, Joginder Singh; Sharma, Rakesh Kumar (Prabandhan: Indian Journal of Management, 2014)
Social audit is an important and effective tool which ensures transparency and accountability in the implementation of the schemes like NREGS. To curve out corruption and financial irregularities in the fair implementation of NREGS, the need of the hour is to create awareness among the common masses about social audit. The right to information is one of the important tools in this regard. This paper is based on the findings of a case study of a work in Gram Panchayat Sari of Mandi District. This survey is carried out by researchers who firstly collected information through RTI and later interviewed labourers and finally gives suggestions on the basis of data collected. This paper highlights the shortcomings in the implementation of NREGS and also discusses area requiring fine tuning and finally suggesting measures to overcome these bottle necks. This paper is based upon several field visits to the study area to assess the impact of Mahatma Gandhi National Rural Employment Guarantee Scheme. Field visits consisted of filling of questionnaires, collection of supporting data, interviewing the respondents, physical verification of the work, focused group discussion and personal observation. These were supplemented by extensive discussions and conversations with villagers, NGO representatives, RTI information holders, workers and suppliers of raw materials, representatives, and government officials at block and district levels.